Indikasi Jamur Dermatofita pada Jari Kaki Pekerja Batu Alam Di Desa Bobos Kecamatan Dukupuntang Kabupaten Cirebon - Pipin Supenah (Poltekkes Kemenkes Kendari, 2020)
Dermatophytes are a group of fungi that have the ability to digest keratin such as the stratum corneum of the skin (epidermis), hair, nails and cause dermatophytosis. Tinea pedis is caused by a dermatophyte fungal infection often found on the soles of the feet and between the toes. Tinea pedis predisposing factors are the use of old closed shoes every day, the use of socks when working and direct contact with water for a long time. This research is located in Bobos Village, Dukupuntang District, Cirebon Regency and is conducted on natural stone workers who work daily in a humid place because they are often in contact with water and wear boots for a long time. The aim of the study was to identify dermatophyte fungi and the percentage of natural stone workers infected with dermatophyte fungi. The method used in this research is descriptive analysis by conducting a survey. The results of identification of dermatophyte fungi on the sidelines of the fingers of natural stone workers were found Trichophyton rubrum and Trichophyton mentagrophytes.